How ‘gangsters’ become jihadists: Bourdieu, criminology and the crime–terrorism nexus - Ilan, Jonathan (European journal of criminology, 2019)
A background in ‘ordinary’ crime, violence and drug use seems to characterize many European individuals recently involved in ISIS-related jihadi violence. With its long tradition of studying marginalized populations and street culture, criminology offers novel ways to explore these developments theoretically. In this article, we demonstrate how Pierre Bourdieu’s concepts of capital, habitus and field allow for a nuanced analysis of how certain individuals move from street to politico-religious criminality. We show that ‘investments’ in street capital can be expended within the field of violent jihadism. We argue that an embodied street habitus supports continuities in attitudes and behaviours within different violent contexts, and furthermore that street social capital facilitates recruitment to violent jihadism. Finally, reflection is offered on resonances between street and jihadi fields. The article explains how continuities in lifestyle can exist between the European city and a Middle Eastern battleground.